Dorsal wrist ganglia treated with arthroscopic "dry technique". Two years followup. - Agustin Guillermo Donndorff; Gerardo Luis Gallucci; Pablo De Carli (Revista de la Asociación Argentina de Ortopedia y Traumatología, 2017)
Background: The purpose of this study is to describe the medium-term results of arthroscopic resection of dorsal wrist ganglia using the “dry technique".